APC-dependent suppression of colon carcinogenesis by PPARγ - Girnun, Geoffrey D. (The National Academy of Sciences, 2002)
Activation of PPARγ by synthetic ligands, such as thiazolidinediones, stimulates adipogenesis and improves insulin sensitivity. Although thiazolidinediones represent a major therapy for type 2 diabetes, conflicting studies showing that these agents can increase or decrease colonic tumors in mice have raised concerns about the role of PPARγ in colon cancer. To analyze critically the role of this receptor, we have used mice heterozygous for Pparγ with both chemical and genetic models of this malignancy. Heterozygous loss of PPARγ causes an increase in β-catenin levels and a greater incidence of colon cancer when animals are treated with azoxymethane. However, mice with preexisting damage to Apc, a regulator of β-catenin, develop tumors in a manner insensitive to the status of PPARγ. These data show that PPARγ can suppress β-catenin levels and colon carcinogenesis but only before damage to the APC/β-catenin pathway. This finding suggests a potentially important use for PPARγ ligands as chemopreventative agents in colon cancer.